The Rate of Return to Storing Wines - Krasker, William S. (Journal of Political Economy, 1979)
This paper contains an empirical investigation of the rate of return to storing wine. The view commonly expressed in the wine literature that this return is very large is found to be inconsistent with the recent history of wine prices. In fact, the data suggest that the expected return to storing wine is no larger than the return to riskless assets.